IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT THROUGH STORY MAPPING AT GRADE VIII MTS MUHAMMADIYAH 22 PADANGSIDIMPUAN - Suleha, Siti (jurnalalfa, 2023)
The aims of the research to determine the improvement of students’ reading skill after using story mapping in understanding narrative text. In this study, the research used quantitative methods with the type of Classroom Action Research (CAR). The population in this study were eight grade students of Mts Muhammadiyah 22 Padangsidimpuan as the sample. The total number of students in the eighth grade is 23 students. The technique of collecting data using multiple choice can be seen from the increase in students’ abilities from the result of the pretest to the posttest. The last data showed average score of 3.47 % of the 15 students exceeded the KKM. The latest data show the students gave met or exceeded the KKM achievement target of 30 %. Based on the data, it could be concluded that using story mapping in teaching narrative text can improving the students’ understanding of narrative text.